Intuitionistic Fuzzy $D^*$-Metric Spaceand Some Topological Properties - Vali, Masoumeh (Journal of Informatics and Mathematical Sciences, 2012)
The notion of intuitionistic fuzzy metric space was introduced by Park [Chaos Solitons and Fractals 22(2004), 1039--1046] and the concept of $D^*$-metric space by Sedghi, Shobe and Zhou [Fixed Point Theory and Applications 2007, {Article ID 27906, 13 pages]. In this paper, we define intuitionistic fuzzy $D^*$-metric space and study precompactness and metrizability in this new setup.